2021
DOI: 10.1371/journal.pone.0257684
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of social interactions and risk factors relevant to the spread of infectious diseases at hospitals and nursing homes

Abstract: Ensuring the safety of healthcare workers is vital to overcome the ongoing COVID-19 pandemic. We here present an analysis of the social interactions between the healthcare workers at hospitals and nursing homes. Using data from an automated hand hygiene system, we inferred social interactions between healthcare workers to identify transmission paths of infection in hospitals and nursing homes. A majority of social interactions occurred in medication rooms and kitchens emphasising that health-care workers shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…A limited number of studies have used wearable sensor technology to study CPIs in hospitals. Some have relied on sensors worn only by HCWs, interacting with each other (9) or with fixed-point sensors which interact with the sensors worn by HCWs (10,11). Before the COVID-19 pandemic, studies using sensors worn by patients and HCWs have been conducted in paediatrics (12), geriatry (13), acute care (14) and long-term care (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies have used wearable sensor technology to study CPIs in hospitals. Some have relied on sensors worn only by HCWs, interacting with each other (9) or with fixed-point sensors which interact with the sensors worn by HCWs (10,11). Before the COVID-19 pandemic, studies using sensors worn by patients and HCWs have been conducted in paediatrics (12), geriatry (13), acute care (14) and long-term care (15).…”
Section: Discussionmentioning
confidence: 99%
“…The average number of hours per 24 hour period during which individuals of type x were present in the ward, x H , was estimated by taking the average total time individuals of type x were present (\emph{i.e.} carrying the captor) and normalising to T , the total duration of the investigation in the ward (Equation [11]).…”
Section: Subhead 3: Prediction Of the Epidemic Riskmentioning
confidence: 99%
“…Several models have quantified the relative burden of SARS-CoV-2 infection and transmission among patients and HCWs over the course of the pandemic. HCWs were identified as being at high risk of occupational exposure to infection, either from colleagues or patients [14][15][16]. During the first wave in early 2020, they have been estimated to be the most important source of onward nosocomial transmission, both to patients and other HCWs [17,18].…”
Section: Insights On Sars-cov-2 Acquisition Routes and Transmission Riskmentioning
confidence: 99%
“…Several studies have found that, when available, PPE use is highly effective for reducing infection risk among both HCWs and patients. Although predicted reductions in infection risk naturally depend on assumptions underlying PPE's impact on viral transmissibility, which vary considerably across studies and for which data are sorely lacking, several studies suggest that widespread PPE use remains a key SARS-CoV-2 prevention strategy, even when conferring comparatively low levels of protection [15,29,37,[48][49][50]. By preventing infection, PPE use has also been shown to reduce HCW workplace absence [37] and workday loss [22].…”
Section: Evaluating Impacts Of Personal Protective Equipment (Ppe)mentioning
confidence: 99%
See 1 more Smart Citation